Design of double layer satellite constellation based on distributed satellite clusters - Ji JIANG; Mugen PENG; Wenbo WANG (Dianxin kexue)
Nowadays,the land communication system is unable to support the complex information needs,and realizing global seamless coverage and high capacity through space information network is anticipated.The existing satellite network is mainly composed of single satellite constellation,which absents the cooperation between the low earth orbit (LEO) satellites and geostationary orbit (GEO) satellites.A double-layer satellite constellation based on distributed satellite clusters was proposed,in which the infrastructure layer was composed of LEO satellites,the communication between LEO satellites was accomplished over inter-satellite links (ISL),and GEO satellites enhance the performance of coverage in low and middle latitudes.As simulation results show,the proposed approach can realize excellent global multiple coverage only relying on the deployment of satellite earth stations in China.